THE HYPOGLICEMIC EFFECT OF AVOCADO SEED (PERSEA AMERICANA MILL) AND HISTOPHATOLOGIC PROFILE - EM SUTRISNA,; TANTI AZIZAH, S,; YUNITA EBRILIANTI OKTARIA, (International Journal of Pharma and Bio Sciences, 2015)
Avocado (Persea Americana Mill) are plants that can be used in the treatment of diabetic mellitus empirically. In everyday life, avocado seed is often not utilized. The aim of this study is to investigate the antidiabetic activity of 96% ethanolic extract of avocado seed (Persea Americana Mill) on wistar rats induced by alloxan. Twenty five rats were divided into 8 treatment groups. Negative control group was treated by distilled water, the positive control group was treated by glibenclamide at dose of 0.45 mg / bw, group I, II, and III were treated by 96% ethanol extract of avocado seeds at doses of 300; 600 and 1200 mg / bw respectively. Before they were treated, all rats were treated by alloxan 150 mg / bw intraperitonial. Day 3 after induction, the rats were treated by extract for 7 days orally. Measurement of glucose was done at day 0, 3 and 10. Blood glucose levels on day 7 were analized by Kruskall-Wallis test followed by Mann-whitney with 95% confidence interval. The results show the 96% ethanol extract of avocado seeds at doses of 300; 600 and 1200 mg / bw can reduce blood glucose levels on rats induced by alloxan.